THE CONCEPT OF INTEGRATED HOLISTIC EDUCATIONAL SYSTEM (IHES): AN ALTERNATIVE FOR ISLAMIC WORLD EDUCATIONAL SYSTEM AS IMPLEMENTED IN SEVEN SKIES ISLAMIC INTERNATIONAL SCHOOL KUALA LUMPUR MALAYSIA - Arianto, Toni; Supriyatno, Triyo (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
The need for an Integrated and Holistic educational system in the Muslim world is a response to dilemma and confusion in finding and establishing so-called integrated education among Muslim countries as a result of bifurcation or dualism in the educational system. The most crucial crisis faced by contemporary Muslims is the existence of educational dualism namely the national, modern secular system and the traditional, Islamic religious system. Many have seen the result and product of those two systems and have dissatisfied when they realized that their children as the product of the system cannot grow in a balanced and overall development of the individual, i.e spiritual, intellectual, imaginative, physical, scientific, linguistic both individually and collectively. In sum, the ultimate of Islamic education is in the realization of complete submission to Allah on the level of the individual, the community, and humanity at large.